Scientific Production on Open Access: A Worldwide Bibliometric Analysis in the Academic and Scientific Context - Miguel, Sandra; Tannuri de Oliveira, Ely Francina [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Mdpi, 2016)
This research aims to diachronically analyze the worldwide scientific production on open access, in the academic and scientific context, in order to contribute to knowledge and visualization of its main actors. As a method, bibliographical, descriptive and analytical research was used, with the contribution of bibliometric studies, especially the production indicators, scientific collaboration and indicators of thematic co-occurrence. The Scopus database was used as a source to retrieve the articles on the subject, with a resulting corpus of 1179 articles. Using Bibexcel software, frequency tables were constructed for the variables, and Pajek software was used to visualize the collaboration network and VoSViewer for the construction of the keywords' network. As for the results, the most productive researchers come from countries such as the United States, Canada, France and Spain. Journals with higher impact in the academic community have disseminated the new constructed knowledge. A collaborative network with a few subnets where co-authors are from different countries has been observed. As conclusions, this study allows identifying the themes of debates that mark the development of open access at the international level, and it is possible to state that open access is one of the new emerging and frontier fields of library and information science.
Keywords: open access; scientific production on open access; bibliometric analysis